BTEX: Desenvolvimento de barras de extração sortiva, determinação em efluente hospitalar e degradação por meio de fotocatálise heterogênea com TiO2 suportado em polímeros - Silva, Daiane Skupin da (2012)
In this work were developed low cost bars of sorptive extraction, using commercial adhesive based on polydimethylsiloxane (PDMS) for the preconcentration and determination of benzene, toluene, ethylbenzene and xylene (BTEX) in effluent from the University Hospital of Santa Maria (HUSM). It was applied multivariate fractional factorial design (26-2) to investigate the significance of the independent variables for the sorptive extraction of BTEX. The best conditions in aqueous solution and in hospital effluent were: 25 °C and 15 min of adsorption, 35 °C and 30 min of desorption, pH 9. Thus, in aqueous solution it was obtained recovery rates of BTEX between 72.2 74.0%, with RSD between 5.4 and 6.4%, while, for hospital effluent spiked with the analytes, the recovery rates ranged around 72.0 74.8% with RSD between 4.68 and 5.62%. The concentrations of benzene, toluene, ethylbenzene and xylene found in the effluent of HUSM were, respectively: 1.2 μg L-1 (RSD 4.6%), 10.4 μg L-1 (RSD 2.1%), 1.7 μg L-1 (RSD 4.4%), 15.8 μg L-1 (RSD 3.5%). The use of bars of sorptive extraction of PDMS have been eliminated the morose stage of vacuum filtration of the effluent and allowed the determination of volatile compounds as BTEX by HPLC-FLD, which to the best of our knowledge, there are not reported in the literature yet. As remediation methodology was applied oxidative processes, heterogeneous photocatalysis and direct photolysis, it was used a stirred tank reactor with thermostatic jacket. Ultraviolet radiation (UV) was generated by mercury vapor lamp medium pressure, 125 W and 401 W m-2. Polymer bars were prepared with polydimethylsiloxane (PDMS) or polyurethane (PU) and TiO2 supported in order to evaluate the degradation of BTEX in aqueous solution and in effluent hospital by heterogeneous photocatalysis. The polymer bars were tested in the absence of UV radiation and the results showed that the analytes do not adsorb themselves in a irreversible way, in both kinds of polymer bars, which could mask the photodegradation. The overall efficiency of the system with TiO2 immobilized, for samples of effluent, is higher than with TiO2 in suspension (and for direct photolysis). To the aqueous solution, fully transparent, the direct photolysis showed better efficiency in the degradation of BTEX. The best conditions for the factorial design (33-1) to the complete degradation of BTEX in aqueous solution were: 20 °C, pH 5 and photolysis (irradiation without TiO2 polymer bars). For hospital effluent in wastewater spiked with the analytes the best conditions were: 20 °C, pH 9 and the use of irradiation with PDMS/TiO2 bars. At 120 min of irradiation it happens the degradation of 100% for all analytes, but the reduction of Chemical Oxygen Demand (COD) was around 25% in hospital effluent. Using a stirred tank reactor, with benzene as a model compound, in toxicity tests with the bioindicator Artemia salina, the reduced of LC50 was 65% compared with the LC50 of the effluent without treatment.